2009
DOI: 10.4049/jimmunol.0800574
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Heparan Sulfate Proteoglycan Syndecan-1 (CD138) in Delayed-Type Hypersensitivity

Abstract: The cell surface heparan sulfate proteoglycan syndecan-1 (CD138) modulates the activity of chemokines, cytokines, integrins, and other adhesion molecules which play important roles in the regulation of inflammation. We have previously shown that syndecan-1-deficient murine leukocytes display increased interactions with endothelial cells and increased diapedesis in vivo and in vitro. In this study, we demonstrate that syndecan-1 has an important function as a negative modulator in the murine contact allergy mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
2
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 53 publications
2
55
2
1
Order By: Relevance
“…Recent results suggest that Sdc1 modulates the direct interaction of ICAM-1 with its integrin counterreceptor, because CD18-blocking antibodies are able to reduce increased binding of Sdc1 KO PMN cells to ICAM-1. 12 In contrast to ICAM-1, no difference in E-selectin and P-selectin binding was observed between Sdc1 KO and wild-type neutrophils. These findings are in accordance with previous intravital microscopy data, suggesting that integrin-mediated tight leukocyte adhesion, rather than selectin-dependent leukocyte rolling, is primarily affected in Sdc1 KO mice.…”
Section: Sdc1 and Dss Colitismentioning
confidence: 86%
See 2 more Smart Citations
“…Recent results suggest that Sdc1 modulates the direct interaction of ICAM-1 with its integrin counterreceptor, because CD18-blocking antibodies are able to reduce increased binding of Sdc1 KO PMN cells to ICAM-1. 12 In contrast to ICAM-1, no difference in E-selectin and P-selectin binding was observed between Sdc1 KO and wild-type neutrophils. These findings are in accordance with previous intravital microscopy data, suggesting that integrin-mediated tight leukocyte adhesion, rather than selectin-dependent leukocyte rolling, is primarily affected in Sdc1 KO mice.…”
Section: Sdc1 and Dss Colitismentioning
confidence: 86%
“…19 -21 Increased recruitment of TNF-␣-producing leukocytes in Sdc1 KO mice emerges as a major mechanistic aspect of this phenotype, since Sdc1 modulates leukocyte recruitment and the inflammatory response in experimental models: in Sdc1 KO mice subjected to contact allergies, an increased expression of ICAM-1 relative to wild-type mice was found. 2,12 In addition, a differentially increased leukocyte-endothelial interaction was observed in vitro and in vivo following i.p. TNF-␣ stimulation.…”
Section: Sdc1 and Dss Colitismentioning
confidence: 97%
See 1 more Smart Citation
“…An in vitro adhesion assay showed that the increased adhesion of Sdc1 À/À leukocytes to ICAM-1 was inhibited by a CD18-blocking antibody, which interferes with the binding of ICAM-1 to its leukocyte integrins (CD11/ CD18) [77]. Therefore, Sdc-1 and CD11/CD18 have been proposed as novel MS targets in anti-inflammatory therapy [77].…”
Section: Msmentioning
confidence: 98%
“…It modulates the activity of chemokines, cytokines, integrins, selectins, and other adhesion molecules, and is assumed to be a negative regulator of various inflammatory processes [76,77]. Syndecan-1 deficient (Sdc-1 À/À ) mice show exacerbated disease symptoms in several inflammatory models, such as hypersensitivity and dextran sulfate sodium (DSS)-induced colitis, in which enhanced immune cell infiltration was reported [77,78]. In Sdc-1 À/À mice, EAE is more severe and recovery is impaired [76].…”
Section: Msmentioning
confidence: 99%